ANALISIS INTRUSI AIR LAUT DENGAN PENGUKURAN TOTAL DISSOLVED SOLIDS (TDS), DAYA HANTAR LISTRIK (DHL) DAN SALINITAS AIR SUMUR GALI - Elsa Taufia Snalles; Wathri Fitrada; Sri Yanti Lisha (Lingkar: Journal of Environmental Engineering, 2023)
This study aimed to analyze seawater intrusion by measuring TDS, DHL and Salinity in dug well water on the coast of Pasir Nan Tigo Village. Sampling was carried out in December on the third week. TDS concentration measurements showed that there were three wells that indicated seawater intrusion, Well 1 (1526.4 mg/L), Well 2 (2500.1 mg/L) and Well 3 (2733 mg/L). DHL value measurements showed that there were three wells that indicated seawater intrusion Well 1 (1765 uS/cm), Well 2 (1556.1 uS/cm) and Well 3 (2002.3 uS/cm). Salinity values showed that there were four wells which indicated seawater intrusion Well 1 (12.7 o/oo), Well 2 (15 o/oo), Well 3 (17.9 o/oo) and Well 4 (10.02 o/oo). The effect of the distance of the well from the shoreline on the concentration of TDS and DHL had an effect of 33% while on the Salinity value of 44%. The results showed that there were several wells that indicated seawater intrusion along the coast in Pasir Nan Tigo Village.